Gestão de custos como instrumento de concorrência potencial nas empresas de transporte rodoviário de passageiros – um estudo de caso - Andrade, Larissa Sepúlveda de (2007)
Brazil’s major means of regional integration, the interstate’s highway system of passenger transportation service delivery is responsible for the dislocation of over 140 million travelers each year. The services are provided by private corporations following nation wide regulatory guidelines. The paper aim is to evaluate cost management’s contribution as an essential strategic force towards the company’s sustainability when facing the competition. It utilizes the fundamental of the structure, conduct and performance model with the presence of market regulations and regulatory enforcement, to analyze the potential competition. Cost composition and differentiation appears as structural elements. Cost management, concerning the regulatory agency’s tax policy, stands out as an element of conduct. Empirically, a unique case study was done for a company in Piauí, it started with an exploratory research done through in-depth personal interviews with managers and it consolidated with a quantitative analysis of the cost structure of the company in confrontation with the national average tax structure recommended by the regulatory agency. The results show strong divergence between the companies’ parameters and the national average’s. It also shows that service delivery differentiation is highly utilized by the company as competitive strategy, fact not contemplated in cost management. It concludes that the company doesn’t exploit const management as an important strategy to engage with potential competitors, thus, shows long term competitive fragility.